2017
DOI: 10.1111/jsbm.12348
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing Opportunities across Campus: The Effects of Cognitive Training and Entrepreneurial Passion on the Business Opportunity Prototype

Abstract: We analyze the effects of the program Cognitive Entrepreneurial Training in Opportunity Recognition on the accurate assessment of prototypical viability of business opportunities. The training integrates the principles of experiential learning and is designed to reach students across campus. We also investigate the moderating role of entrepreneurial passion on opportunity recognition learning. We use a quasi‐experimental design with pre‐test, post‐test in two European universities. The results demonstrate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 89 publications
(220 reference statements)
3
72
0
Order By: Relevance
“…The environments, be it technology and or changes in economic as it affects products and services in the market. Changes in the environment are essential, and some are less significant to be identified [8]. Nascent entrepreneurs can identify these changes' opportunities or develop new opportunities provided by those changes and focus on those opportunities through entrepreneurial business actions.…”
Section: A Entrepreneurial Attention and Entrepreneurial Opportunitymentioning
confidence: 99%
“…The environments, be it technology and or changes in economic as it affects products and services in the market. Changes in the environment are essential, and some are less significant to be identified [8]. Nascent entrepreneurs can identify these changes' opportunities or develop new opportunities provided by those changes and focus on those opportunities through entrepreneurial business actions.…”
Section: A Entrepreneurial Attention and Entrepreneurial Opportunitymentioning
confidence: 99%
“…From thinking and/or cognitive current, individuals who are potential entrepreneurs usually detect opportunities and minimize latent risks, this is generally achieved through converting experiences into applied knowledge (Miller & Le Breton-Miller, 2017;Tipu, 2015). Studies in this context have shown that the behavior and entrepreneurial passion of individuals is focused on creating, developing, and inventing new ways of doing things, facing problems, and/or creating new prototypes and that it also manages to develop positive impulses, which promote the strengthening of the intentions to undertake (Costa, Santos, Wach, & Caetano, 2018;Neneh, 2019). From the theoretical and empirical review, we emit the following hypothesis (view Figure 1):…”
Section: The Entrepreneurial Passion and The Relationship With The Unmentioning
confidence: 99%
“…Entrepreneurial passion is a core trait that entrepreneurs must possess, which can encourage entrepreneurs to conduct entrepreneurial behaviors. When entrepreneurs face difficulties, entrepreneurial passion can be used as a support force to keep them going (Costa et al, 2018;Montiel-Campos, 2018). By persisting in entrepreneurial behavior, relentlessly pursuing established goals, and investing a lot of time and energy, entrepreneurs can achieve successful entrepreneurship and obtain economic benefits (Milanesi, 2018).…”
Section: Introductionmentioning
confidence: 99%